2012
DOI: 10.1097/acm.0b013e31825803f3
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Physician Specialty Training in Canada and the United States

Abstract: Today's interconnected world has produced a distinct need for physician specialists in public health and preventive medicine. As the industrialized world confronts aging populations, rising health care costs, and a growing epidemic of chronic disease, it is clear that the focus of health care must become more preventive than curative.Although public health and preventive medicine exists in various forms worldwide, the literature has not yet examined different national strategies for postgraduate medical traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…There is a large variety of public health work across countries [ 20 ]. The educational system and jobs of PHPs differ between the United States and Canada [ 21 ], and PHPs in Korea have some clinical work, in contrast to Japanese PHPs [ 11 ]. The results of our study cannot be directly applied to other countries; however, physicians’ clinical careers, especially board certifications, should be considered for PHP recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…There is a large variety of public health work across countries [ 20 ]. The educational system and jobs of PHPs differ between the United States and Canada [ 21 ], and PHPs in Korea have some clinical work, in contrast to Japanese PHPs [ 11 ]. The results of our study cannot be directly applied to other countries; however, physicians’ clinical careers, especially board certifications, should be considered for PHP recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, research on PH personnel and specialists also show unclear roles and insertion in national health systems. [32] An uncertain identity was also found in research from Singapore which found that PHM was “difficult to characterise” due to its intrinsically context-specific focus–improving population health, and multi-disciplinary orientation, with competencies defining professional status and roles. [33] The recognition of the contextual nature and broad scope of PH practice led the UK speciality to incorporate non-medically trained professionals,[34] and it is surprising that a multi-disciplinary speciality has not been adopted elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…Although the need for continuing PH education for PH specialists is advocated for the PH workforce globally (40), this was not raised by respondents in our study. It is, however, highlighted in current Australian literature (39), and is required in the USA and Canada (41).…”
Section: Discussionmentioning
confidence: 99%